2008
DOI: 10.4038/jnsfsr.v36i2.146
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sequence characterized amplified region (SCAR) markers linked to sex expression in <i>Carica papaya</i> L.

Abstract: Carica papaya L. exhibits monoecious and dioecious plants that usually take six months for phenotypic manifestation. Nursery culling aided by sex-specific DNA markers was envisaged to alleviate the unnecessary cost incurred by farmers for maintaining unproductive male plants that contribute to 40-50% of the population. The mechanism of sex determination in papaya has been described as a tri-allelic single gene system with alleles, M 1 -dominant for maleness, M 2 -dominant for hermaphrodism and m-recessive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This may be due to either small size of the fragment obtained during initial characterization or a single base differences or single base mutation at the primer. The result is in agreement with Niroshini et al (2008) in papaya. However, the SCAR marker SCF/R-01 was monomorphic and did not discriminate female from male plants.…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to either small size of the fragment obtained during initial characterization or a single base differences or single base mutation at the primer. The result is in agreement with Niroshini et al (2008) in papaya. However, the SCAR marker SCF/R-01 was monomorphic and did not discriminate female from male plants.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the availability of an optimized protocol for DNA characterization to estimate the genetic diversity and to ensure genetically representative non-redundant samples is of great interest [41]. In this sense, universal RAPD markers can be a most suitable in the molecular characterization of C. cubensis accessions and to construct efficient core collections as has been described by Bortolini [42] in white clover complementary to the application of more recent developed markers in C. papaya of dominant SPAR (Single primer amplification reaction) [17] and SCAR (sequence characterized amplified region) markers [25], and codominant SSR (Single sequence repeat) markers [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…This results in differential amplification of regions that vary in primer site sequence resulting in polymorphic amplification products usually analyzed as presence/ absence. These markers have been previously assayed in the molecular characterization of Carica papaya cultivars [15][16][17][18] and some wild related species [14,19,20], the identification of flower sex types [8,[21][22][23][24][25] and development of genetic linkage maps [26]. In addition, to improve the capacity of the molecular characterization assays using these PCR-based markers, multiplex PCR, a variant of the PCR in which more than one target sequence is amplified using more than one pair of primers are being assayed [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided preliminary data indicating that random amplifi ed polymorphic DNA (RAPD) markers might be useful for detecting sex expression in papaya (SONDUR et al 1996, SOMSRI et al 1998, NIROSHINI et al 2000, 2008, PARASNIS et al 2000, LEMOS et al 2002, URASAKI et al 2002a, but these reports utilized a relatively small number of plants. However, DEPUTY et al (2002) reported SCAR markers that are specifi c for male and hermaphrodite plants in a large number of plants.…”
Section: Discussionmentioning
confidence: 99%
“…As the segregation in this case is also 1:1 for female to hermaphrodite, identifi cation at the early stage is desirable. Molecular markers have been studied earlier for sex determination in papaya (SONDUR et al 1996, SOMSRI et al 1998, PARASNIS et al 1999, NIROSHINI et al 2000, 2008, URA-SAKI et al 2002a, b, DEPUTY et al 2002, LEMOS et al 2002. Recently a transcriptomics study has been conducted for sex determination in papaya (URASAKI et al 2012).…”
Section: Introductionmentioning
confidence: 99%